2016
DOI: 10.1242/dev.141291
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evolution in blind cavefish is driven by early embryonic events during gastrulation and neurulation

Abstract: Natural variations in sensory systems constitute adaptive responses to the environment. Here, we compared sensory placode development in the blind cave-adapted morph and the eyed riverdwelling morph of Astyanax mexicanus. Focusing on the lens and olfactory placodes, we found a trade-off between these two sensory components in the two morphs: from neural plate stage onwards, cavefish have larger olfactory placodes and smaller lens placodes. In a search for developmental mechanisms underlying cavefish sensory ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
107
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 91 publications
12
107
2
Order By: Relevance
“…Three of these observations were in adult fish (Hüppop 1987;Yoshizawa et al 2010;Wilkens and Hüppop 1986), and two supported that the enhanced skills were already in place as early as 25 days after birth (Espinasa et al 2014;Hinaux et al 2016). For example, Hüppop (1987) showed that under competitive conditions, cavefish found about 80% of all pieces of beef-heart muscle provided in the dark whereas the epigean fish were successful at finding only 20%.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Three of these observations were in adult fish (Hüppop 1987;Yoshizawa et al 2010;Wilkens and Hüppop 1986), and two supported that the enhanced skills were already in place as early as 25 days after birth (Espinasa et al 2014;Hinaux et al 2016). For example, Hüppop (1987) showed that under competitive conditions, cavefish found about 80% of all pieces of beef-heart muscle provided in the dark whereas the epigean fish were successful at finding only 20%.…”
Section: Introductionmentioning
confidence: 83%
“…Multiple morphological and behavioural attributes have been described to support this statement, such as a higher number of taste buds (Yamamoto et al 2009;Varatharasan et al 2009), higher chemosensory capabilities (Protas et al 2008;Bibliowicz et al 2013;Hinaux et al 2016), an enhanced number of cranial neuromasts (Yoshizawa et al 2012), modulation in early developmental signalling pathways influencing brain development and organization (Yamamoto et al 2004;Pottin et al 2011), and a behaviourally more efficient posture with respect to the substrate when bottom feeding (Schemmel 1980).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…from single cell creatures to multicellular creatures, and from aquatic creatures and amphibian to terrestrial mammals [ Figure 3]. Furthermore, some evolutionarily conserved molecular networks such as HOX, Hedgehog, and Myc play important roles in the developmental process [66][67][68][69][70][71][72] , indicating development and evolution share some inherent mechanisms. During the past 20 years, the discovery of conserved gene networks that control embryonic development and the ability to examine genomic records has revolutionized Darwinian evolutionism that animal relationships had to be deduced by observation of external morphological characteristics.…”
Section: Development and Evolution (Dev-evo) A Novel Hypothesis Relamentioning
confidence: 99%